Slave Life in Virginia and Kentucky : A Narrative by Francis Fedric, Escaped Slave - Innes, C. L. (Book collections on Project MUSE., 2010)
In 1854, faced with the threat of yet another brutal beating, a fifty-year-old slave in Mason County, Kentucky, decided to try again to escape. His first attempt had ended in his near starvation as he hid for nine weeks in a swamp, before hunger compelled him to return to his master. This time the slave sought the help of a neighbor with abolitionist sympathies, and he joined the hundreds of other fugitive slaves fleeing across the Ohio River and north to Canada on the Underground Railroad. After his arrival in Toronto he discarded his master's surname (Parker), renamed himself Francis Fedric.